2022
DOI: 10.3390/ijms23084195
|View full text |Cite
|
Sign up to set email alerts
|

Remodeling and Fibrosis of the Cardiac Muscle in the Course of Obesity—Pathogenesis and Involvement of the Extracellular Matrix

Abstract: Obesity is a growing epidemiological problem, as two-thirds of the adult population are carrying excess weight. It is a risk factor for the development of cardiovascular diseases (hypertension, ischemic heart disease, myocardial infarct, and atrial fibrillation). It has also been shown that chronic obesity in people may be a cause for the development of heart failure with preserved ejection fraction (HFpEF), whose components include cellular hypertrophy, left ventricular diastolic dysfunction, and increased ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 214 publications
1
21
0
Order By: Relevance
“…It is well known that neutrophils and/or macrophages show a strong affiliation to invade the damaged area due to the apoptotic cardiomyocytes and the need for their removal; however, in the present paper, we did not evaluate the cell subpopulations infiltrated [ 6 , 30 ]. Our data are in line with several studies that have demonstrated that MetS signs, such as obesity, insulin resistance, lipotoxicity, and inflammation, play an important role in myocardial fibrosis by activating several downstream signaling cascades [ 31 , 32 , 33 ]. In addition, scientific evidence has implicated angiotensin II in the inflammatory process as well as in the progression of myocardial fibrosis via binding to AT1 receptor [ 34 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…It is well known that neutrophils and/or macrophages show a strong affiliation to invade the damaged area due to the apoptotic cardiomyocytes and the need for their removal; however, in the present paper, we did not evaluate the cell subpopulations infiltrated [ 6 , 30 ]. Our data are in line with several studies that have demonstrated that MetS signs, such as obesity, insulin resistance, lipotoxicity, and inflammation, play an important role in myocardial fibrosis by activating several downstream signaling cascades [ 31 , 32 , 33 ]. In addition, scientific evidence has implicated angiotensin II in the inflammatory process as well as in the progression of myocardial fibrosis via binding to AT1 receptor [ 34 ].…”
Section: Discussionsupporting
confidence: 91%
“…In I/R injury, expression of MMP-2 is of particular interest because MMP-2 degrades extracellular matrix substrates including Type IV collagen, laminin, elastin, interstitial fibrillar collagen, and sarcomeric proteins [ 35 , 36 ]. The expression of this zinc-dependent protease is regulated by mechanical signals, inflammatory factors, hormones, and NPs, among other factors; some authors even suggest that MMP-2 can be used as a possible pharmacological target in the treatment of heart failure [ 31 , 36 , 37 , 38 ]. Therefore, we analyzed the expression of MMP-2 in all experimental groups and found that the expression of this enzyme was higher in hearts from MetS rats in sham-operated conditions and under I/R damage without there being changes in the Ct group.…”
Section: Discussionmentioning
confidence: 99%
“…Cardiac fibrosis is a common feature observed in obesity, which ultimately leads to myocardial stiffness, arrhythmias and diastolic dysfunction [ 10 , 36 ]. Previous studies have confirmed the detrimental role of TTR in cardiac cells, showing toxic effects on cardiac myocytes [ 37 ]; however, there are no studies evaluating the effects of TTR on extracellular matrix synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…Fibrosis is defined as excessive extracellular matrix accumulation, which could be due to an increase in extracellular matrix protein synthesis and/or a decrease in its degradation. It is a well-recognized cause of high morbidity and mortality, increasing myocardial stiffness and, therefore, promotion of diastolic dysfunction [ 9 , 10 ]. Furthermore, its evaluation has been suggested as a useful indicator of long-term mortality in heart failure patients [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…The 2018 population survey found that 27% of the Greenlandic population were obese [ 16 ] and 32% of the HF population in the UK [ 10 ]. Suggesting that obesity among Greenlandic Inuit induce HF through pathologic pathways such as insulin resistance, inflammation of adipokines and cardiac lipotoxicity as well as increased predisposition to established risk factors for HF [ 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%